Perceptions of Carriership of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Bacteria: A Qualitative Study - Karin Uggla; Robin Razmi; Josef D. Järhult; Maria Lindberg (MDPI AG, 2024)
The spread of antimicrobial resistance is a global health concern, and resistance mediated by Extended-Spectrum Beta-Lactamases (ESBLs) can cause major consequences. The aim of this study was to explore individuals' perceptions of their daily life and how they cope after being diagnosed with carriage of ESBL-producing bacteria. A qualitative study was conducted with a descriptive design. Data were collected through individual interviews with 24 persons having ESBL carriership, via a semi-structured interview guide. The data were analyzed using qualitative content analysis. The informants' perceptions on "Living with uncertainty about carriership that impacts oneself and others" were interpreted. Experiences of altered behaviors and sentiments due to ESBL carriership were described, as ESBL carriership was perceived to have a psychosocial impact on many informants. Ambiguous and inconsistent information tended to exacerbate these perceptions. The results of this study emphasize the importance of conveying individualized information, both at the time of diagnosis of ESBL carriage and thereafter. This study was not registered.